The occupation of Japan 1945-1952 Tokyo, Washington, and Okinawa - Fukunaga, Fumio 1953-
Following its defeat in World War II, Japan was placed under the control of SCAP GHQ headed by General Douglas MacArthur. Initially, the Occupation promoted policies of demilitarization and democratization. A new Japanese constitution which pursued pacifism was established. However, as the Cold War intensified, policies switched in the direction of economic recovery, and it was contended that Japan should take the anti-Communist pro-America path. In 1951, at the height of the Korean War, the San Francisco Peace Treaty and the Japan-U.S. Security Treaty were concluded as a fixed set. Winner of the 2015 Yomiuri Yoshino Sakuzo Prize for academic writing on politics, economics, and history, this book provides a wide view of the seven years of the Occupation of Japan which led to the 'postwar system' that has continued into the twenty-first century.